Republic of Mozambique : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents an update to the Report on the Observance of Standards and Codes on Fiscal Transparency Module for the Republic of Mozambique. Several measures that respond to the earlier recommendations are now being implemented. The Ministry of Planning and Finance has already started gathering information and establishing procedures to include self-generated revenues of ministries and government agencies and their related expenditures in the budget, beginning with the 2003 budget. Public availability of fiscal information has been enhanced by the publication of quarterly budget execution reports.